Emerging mechanisms of lipid peroxidation in regulated cell death and its physiological implications - Zheng, Yongxin; Sun, Junlu; Luo, Zhiting; Li, Yimin; Huang, Yongbo (Cell death & disease, 2024)
Regulated cell death (RCD) refers to the form of cell death that can be regulated by various biomacromolecules. Each cell death modalities have their distinct morphological changes and molecular mechanisms. However, intense evidences suggest that lipid peroxidation can be the common feature that initiates and propagates the cell death. Excessive lipid peroxidation alters the property of membrane and further damage the proteins and nucleic acids, which is implicated in various human pathologies. Here, we firstly review the classical chain process of lipid peroxidation, and further clarify the current understanding of the myriad roles and molecular mechanisms of lipid peroxidation in various RCD types. We also discuss how lipid peroxidation involves in diseases and how such intimate association between lipid peroxidation-driven cell death and diseases can be leveraged to develop rational therapeutic strategies.